Inhomogeneous Cosmological Models in Bimetric Theory of Gravitation - Tripathy, S. K.; Behera, D.; Sahoo, P. K. (Communications in Physics, 2012)
Plane symmetric inhomogeneous cosmological models for perfect fluid distribution are investigated in the frame work of Rosen’s bimetric theory of gravitation. A negative pressure corresponding to false vacuum state is considered. Some of the physical and kinematical properties of the models are discussed